How Do Nursing Students Perceive the Needs of Older Clients? Addressing a Knowledge Gap. (14th January 2016) - Hirst, Sandra P.; Lane, Annette M.
Abstract : Background . Many nurse educators understand that students need to embrace the challenges and rewards of working with older clients. Yet, they might wonder how they can help students to develop and what is the specialized knowledge necessary to care for older clients. Question . How do students perceive the nursing needs of older adults? Method . A qualitative descriptive study was undertaken. Data collection occurred through semistructured interviews (9 students) and one focus group (8 students) using a photoelicitation technique. The researchers used a descriptive approach to analyze the data. Findings . Six themes emerged from the data: ask the older client!; physiology rules; personal, not professional; who can validate?; hierarchy of needs; and help us learn. Conclusion . Participants relied upon previous patterns of learning, primarily experiential, and on the views of health care colleagues in clinical practice to make decisions about the health needs of older clients. Participants clearly recognized the need to and significance of understanding the health care requirements of older clients. Findings have implications for how the care of older clients is introduced into nursing education programs.